In vivo screening of diterpene alkaloids using bdelloid rotifer assays - Kiss Tivadar (ACTA BIOLOGICA HUNGARICA, 2017)
The group of diterpene alkaloids contains numerous compounds with complex chemistry and diverse pharmacological activities. Beside toxicity, these compounds possess activity on the cardiovascular system, tumor cell lines and nervous system. The pharmacological properties have been described using in vitro and in vivo techniques; however, the bioactivities of many compounds have not thoroughly been studied. Here we report on the in vivo evaluation of ten diterpene alkaloids using bdelloid rotifer assays. Napelline exerted toxic effects on rotifers, while wide tolerance range was observed for other investigated compounds. Weak toxicity of songorine is supported by our experiment. Toxicological data for senbusine A, senbusine C, septentrioidine and hetisinone are reported for the first time.